Šole govorijo - Batič, Matic (Prispevki za novejšo zgodovino, 2023)
This article explores the ideological language of school buildings in the Gorizia (Goriška) region between 1918 and 1943. At the time, education represented one of the pillars of the Italianisation process, carried out by the Italian authorities to destroy the Slovenian ethnic community beyond the Rapallo border. The intense ideologisation of education was also evident from the symbolic implications of school buildings. The latter did not merely represent neutral physical facilities where classes were held. Instead, they were places full of meaning. The symbolic charge of the school premises was established in various ways. While the characteristics and purpose of schooling played the most crucial role in this, many school buildings were also additionally symbolically marked – mainly through their names but also with the state and fascist symbols featured on the school premises. The symbolic character of Italian schools at that time is best illustrated by the numerous arsons and attempted arsons carried out by the Slovenian resistance organisation TIGR.
Keywords: education; fascism; fašizem; Goriška; Italianisation; italijanizacija; school buildings; šolske stavbe; šolstvo; the Gorizia region